Duality of resurrection and doped reality: a reading in the poetry collection Hunger piles by Khalil Hawi. (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Modern Arabic poetry is a distinct literary product by knocking, and its dealing  with all Arab human issues, especially political, economic and social issues, Through these topics, so it is the mirror of the times, and the image of the Arab man appears loaded with the burdens and worries of life  Therefore, this research aims to examine the experience of the poet Khalil Hawi through his collection hunger piles, and has a clear impact on the poetic movement in the modern era, by presenting a new reading of this collection, and because it is considered the culmination of modern Arab poetic creativity, with its contents, visions and aspirations.